Reliability and validity of the abbreviated version of the Mindful Eating Questionnaire in Turkish adults - Kaya, Seda; Acik, Murat; Coskun, Ayfer Beyaz; Yilmaz, Feray Cagiran (Pontificia Universidade Catolica Campinas, 2024)
Objective To adapt the abbreviated version of the Mindful Eating Questionnaire to Turkish for the Turkish adult population. Methods This cross-sectional study includes 709 participants aged between 18-65 years living in the province of Elazig. The data was collected through a voluntary face-to-face survey. The questionnaire was included their general characteristics and the Mindful Eating Questionnaire -18 and Eating Attitude Test-26. Confirmatory factor analysis was used to test the validity of the Mindful Eating Questionnaire -18. Statistical analyzes were conducted using the R-Project program and IBM (R) SPSS (R) version 26.0. Results The overall content validity index was 0.93. A confirmatory factor analysis was conducted for the two sub-scales and reduced the abbreviated of Mindful Eating Questionnaire to 18 items. The Cronbach's alpha coefficient was 0.718 for the Mindful Eating Questionnaire-18 total factor scores and Cronbach alpha values for awareness, and disinhibition were found to be 0,843 and 0,789, respectively. The minimum discrepancy per degree of freedom=4.914 and the fit indices were at an acceptable level (RMSEA=0.074, CFI=0.934, SRMR=0.079, TLI=0.925, GFI=0.968, AGFI=0.959). Conclusion The findings of study showed that the psychometric properties of the abbreviated Mindful Eating Questionnaire adapted into Turkish were acceptable through construct and internal consistency reliability for adults.
Confiabilidade e validade de uma versão abreviada do questionário de alimentação consciente em adultos turcos
Keywords: Adaptation; Confirmatory factor analysis; Mindful eating; Reliability; Validity